Minimum wage regulation in Australia in the wake of the pandemic: the future of the five wage concepts?. (2nd October 2021) - Hamilton, Reg; Nichol, Matt
ABSTRACT: The importance of Australia's minimum wage has never been more significant for low-paid workers than during the concurrent crises of wage stagnation and the pandemic. But in this current regulatory paradigm will the minimum wage be able to continue its history of fulfiling its social, economic and industrial objectives? This article will examine this challenge by reviewing how Australia's minimum wage has been calculated by an independent industrial tribunal through assessing the needs of workers, the capacity of employers to pay, and the function of the minimum wage as a safety net. Maintenance of the high level of the minimum and whether any groups of workers are left behind are key issues for the future of minimum wage regulation.